2021
DOI: 10.3389/fnrgo.2021.646225
|View full text |Cite
|
Sign up to set email alerts
|

Brain Oscillation Entrainment by Perceptible and Non-perceptible Rhythmic Light Stimulation

Abstract: Objective and Background: Decades of research in the field of steady-state visual evoked potentials (SSVEPs) have revealed great potential of rhythmic light stimulation for brain–computer interfaces. Additionally, rhythmic light stimulation provides a non-invasive method for entrainment of oscillatory activity in the brain. Especially effective protocols enabling non-perceptible rhythmic stimulation and, thereby, reducing eye fatigue and user discomfort are favorable. Here, we investigate effects of (1) percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…It is also important to consider that the success of eliciting SSVEP responses using light stimulation of extremely low contrast and intensity may be, at least partly, related to the surface covered by the flickers. Indeed, it can be argued that the flickers implemented in the present study, but also in previous studies reporting SSVEP responses elicited by imperceptible flickers (Lingelbach et al, 2021;Tsoneva et al, 2023), were rather large. Indeed previous research has shown that flicker size is positively correlated with SSVEP response amplitude (Duszyk et al, 2014;Ng et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is also important to consider that the success of eliciting SSVEP responses using light stimulation of extremely low contrast and intensity may be, at least partly, related to the surface covered by the flickers. Indeed, it can be argued that the flickers implemented in the present study, but also in previous studies reporting SSVEP responses elicited by imperceptible flickers (Lingelbach et al, 2021;Tsoneva et al, 2023), were rather large. Indeed previous research has shown that flicker size is positively correlated with SSVEP response amplitude (Duszyk et al, 2014;Ng et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
“…By decreasing the luminosity of the brightest state of the flicker, which in turn diminishes the amplitude modulation depth, also leads to a reduction in the overall mean luminance intensity of the flickering stimulation. Some studies have demonstrated the feasibility of this method by inducing SSVEP responses using imperceptible flickers with LEDs, where the amplitude modulation depth was reduced below the perceptual visibility threshold (Lingelbach et al, 2021; Tsoneva et al, 2023). While these latter offer interesting insights about the use of such low amplitude depth VEPs, they lack temporal information regarding the signal-to-noise measures over the occipital in response to such stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…-They are perceived as more comfortable than traditionally used sinusoidal stimuli (Dreyer et al, 2017). -They can be evoked reliably even with an intensity below the individual perceptibility threshold and in covert attention conditions without direct fixation of the flickering light source (Lingelbach et al, 2021a;Lingelbach et al, 2021b). -Their amplitude, their perceived flicker intensity, as well as the user comfort during the stimulation are affected by the modulation depths via the modulation index (current manuscript).…”
Section: Discussionmentioning
confidence: 97%
“…They can be evoked reliably even with an intensity below the individual perceptibility threshold and in covert attention conditions without direct fixation of the flickering light source ( Lingelbach et al, 2021a ; Lingelbach et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation